Лиза апайлэн лякиё шобретэз: тодэ ваёнъс, очеркъёс, дэмланъёс / Е. И. Камашева - Камашева Елизавета Ивановна (Удмуртия, 2012)
Экземпляры: чз (20170201) / Инвентарный номер: 52350 / Цена: 20.00 / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: К 18 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)